THE POSSIBILITY OF SUPPLYING THE DEFENSE SYSTEM WITH FOOD PRODUCTS IN CONDITIONS OF DISTURBANCE ON THE MARKET - Nikolić, Srboljub; Mihajlovic, Milan; Damnjanović, Radovan; Savić, Aleksandar; Mišić, Nebojša (Economics of Agriculture, 2023)
Recently, as a result of COVID-19 and the war conflict in Ukraine, the supply system in the world has been very difficult. In addition to the above consequences, a number of other activities lead to disruptions in the market, which complicates the supply system at the global level. The defense system in the conditions of war conflicts is considered unique in defining regulations and procedures and has a special treatment in treating the supply process in such conditions. In this sense, this paper theoretically discusses the food supply system, the available market for food products with reference to the food industry and possible market disturbances and their effect on the supply system. The goal of the work is to find alternative solutions for the supply of food products to the defense system of the Republic of Serbia in conditions of disruptions in the market.